Characterization of Four Monoclonal Antibodies to Factor VIII Coagulant Protein and Their Use in Immunopurification of Factor VIII - Croissant, Marie-Pascale; vande Pol, Hendrik; Lee, Helen H; Allain, Jean-Pierre (Thrombosis and Haemostasis, 1986)
Four monoclonal anti-VIII: C antibodies were obtained from the fusion of the splenocytes of one B alb/C mouse with a specific activity ranging from 2.3 to 45,000 U/mg when purified from ascitic fluid. Only one antibody was able to inhibit completely Factor VIII: C in normal plasma. The four antibodies could bind Factor VIII: CAg in plasma and commercial concentrate both in liquid and solid phase, and were suitable for immunopurification of Factor VIII :C.Three antibodies competed with polyclonal anti-VIII: CAg Fab′ in a liquid phase IRMA, and all of them were able to displace their own binding to Factor VIII: CAg. Competition studies between monoclonal antibodies for the binding to Factor VIII: CAg were performed and showed the recognition of different epitopes and various functional impact. These studies indicate that at least one antibody, with the lowest anti-VIII:C titer clearly recognizes a different epitope of VIII: C than those recognized by the others. Affinity constants ranged from 109 to 1010 l/mole.
Keywords: Monoclonal antibodies; Factor VIII: C; Antibody affinity; Competition studies; Immunopurification